COMPLIANCE AUDIT TERHADAP STANDAR OPERASIONAL PROSEDUR PENJUALAN MOBIL - Adi, Purnomo Sutirto; Retnani, Endang Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to conduct the operational audit in order to find out wheter the Standar Operating Procedure (SOP) of sales has been obeyed by the parties in accordance with the sale of of automobile unit on PT United Indo Surabaya (Nissan Authorized Dealer Jemursari). The qualitative method is used as the research method since the researcher does not prove the hypothesis but to carry out the operational audit. It has been found from the result of the research that the company has implemented the internal control on sales which is shown by the organizational structure, Standar Operating Procedure (SOP), and the healthy pratical on the field, and also competence employees. The Audit result of internal control of the company has found noncomlpliance, which is title transfer cost of Purchase Order and Bank Receipt In where there is no authorization from the authorities. The whole research about weakness, results, and recommendations have been disclosed and reported on the statement of management letter. One of the suggestions is by carrying out the internal control periodically.Keywords: The Statement of Management Letter.